The influence of relative refractive index and core diameter on properties of single-mode optical fiber. - sama aldabagh; Manaf Saeed (College of Education for Pure Sciences, 2020)
A study of the influence of the parameters design, such as the refractive index of the core, the cladding and the radius of the core on propagation constant (β) of single-mode optical fiber in optical communication region (1.2-1.6) m have been investigated. Material, waveguide, and profile dispersions are analyzed and investigated. Three models of optical fibers with different relative refractive indices () (0.004, 0.007, 0.01) at a wavelength equal 1.55 m, and three models of core radius (3,4,5) m is taken in the count. Numerical simulations and modeling are arranged depending on weakly guiding approximation for solving homogeneous wave equation derived from Maxwell's equations. Our modeling solved by the aid of MATLAB software. Material and profile dispersion have no significant change for various relative refractive index, while waveguide dispersion is affected by the change of relative refractive index. the waveguide dispersion increased by increasing core diameter and the profile dispersion decreased as the core diameter increased. There is no effect on martial dispersion by increasing the core diameter.